A Canadian Contribution to the Paleoclimate Model Intercomparison Project (PMIP) - Jetté, Hélène (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTPMIP (Paleoclimate Model lntercomparison Project) is designed to compare and improve the ability of General Circulation Models (GCMs) to simulate a wide range of climatic conditions including known features of past climatic states that are significantly different from present conditions. One of the first simulations of past climate conducted under this project targets the 6000 yr BP period for the following reasons: 1) deglaciation was complete and the last remnants of the Laurentide Ice Sheet had essentially disappeared by this time, 2) sea surface temperatures approached modern values, 3) the orbital insolation regime was the only major boundary condition significantly different from present, and 4) a number of study sites can already be used to provide preliminary paleoenvironmental reconstructions for this period. Contributions from the Canadian scientific community towards this experiment are presented, following a brief overview of Canadian modern environmental conditions which places the regional contributions into a broader perspective.